2014
DOI: 10.1089/ars.2013.5610
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Neuronal Voltage-Gated Calcium Channels

Abstract: Significance: Voltage-gated calcium channels are ubiquitously expressed in neurons and are key regulators of cellular excitability and synaptic transmitter release. There is accumulating evidence that multiple subtypes of voltage-gated calcium channels may be regulated by oxidation and reduction. However, the redox mechanisms involved in the regulation of channel function are not well understood. Recent Advances: Several studies have established that both T-type and high-voltage-activated subtypes of voltage-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 79 publications
(85 reference statements)
0
29
0
Order By: Relevance
“…Thus, in higher organisms, different members of Ca 2+ -conducting ion channels/transporters are known to be redox sensitive (Kozai et al, 2014;Todorovic and Jevtovic-Todorovic, 2014). In the yeast Saccharomyces cerevisiae, it has recently been shown that the yeast vacuolar Ca 2+ channel Yvc1p, a member of the transient receptor potential (TRP) family of Ca 2+ channels, responds to the redox state in the cell to regulate Ca 2+ levels under conditions of glutathione depletion and extracellular oxidative stress through specific glutathionylation of cysteine residues (Chandel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in higher organisms, different members of Ca 2+ -conducting ion channels/transporters are known to be redox sensitive (Kozai et al, 2014;Todorovic and Jevtovic-Todorovic, 2014). In the yeast Saccharomyces cerevisiae, it has recently been shown that the yeast vacuolar Ca 2+ channel Yvc1p, a member of the transient receptor potential (TRP) family of Ca 2+ channels, responds to the redox state in the cell to regulate Ca 2+ levels under conditions of glutathione depletion and extracellular oxidative stress through specific glutathionylation of cysteine residues (Chandel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the peripheral nervous system, Ca V 3 are expressed in several types of sensory neurons, including a subpopulation of small, capsaicin-sensitive (presumed nociceptive) DRG neurons where they influence excitability and so play an important role in nociception. 6,8 Also due to their window currents, Ca V 3.1 and 3.2 strongly influence cell proliferation, as has been studied in vascular smooth muscle and different types of cancers (see 2 ).…”
mentioning
confidence: 99%
“…Their control of burst firing in DRG neurons indicates they are of central importance to nociception since stimulus intensity correlates with burst frequency. 8 Native nociceptive and recombinant CaV3 currents are enhanced by reducing agents (which induce hyperalgesia) and inhibited by the oxidising agents. This sensitivity to redox modulation of Cav3.2 is specific among the Cav3 isoforms, and arises because of the presence of an extracellular, high affinity binding site for trace metals (Zn 2C , Ni 2C ) formed by interacting regions of the S1-S2 and S3-S4 loops within domain I of the channel protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations